Local Service Learning in Teacher Preparation Program - Prasart Nuangchalerm (Intelektual Pustaka Media Utama, 2016)
The local knowledge is a simply integrated in education and learning process. This study aims to promote local knowledge in school through service learning. The learning process is employed herbal plants to reinforce students learn how to sustain local knowledge with modern life and 21st century classroom. Participants consisted of 42 preservice teachers, 11 inservice teachers, and 50 secondary students. Findings revealed that service learning is significantly promoted public mind, self-efficacy, learning satisfaction, and learning process in local knowledge.